Subpolar North Atlantic sea surface temperature since 6 ka BP: Indications of anomalous ocean-atmosphere interactions at 4-2 ka BP. (15th August 2018) - Orme, Lisa Claire; Miettinen, Arto; Divine, Dmitry; Husum, Katrine; Pearce, Christof; Van Nieuwenhove, Nicolas; Born, Andreas; Mohan, Rahul; Seidenkrantz, Marit-Solveig
Abstract: Atmospheric circulation may change with future climate change in response to modification of meridional temperature gradients, but the potential influence on ocean circulation is as yet unclear. Over the mid-late Holocene, atmospheric circulation in the North Atlantic region has fluctuated on millennial timescales; therefore, the ocean response to these changes can be investigated using the paleoceanographic records that have been developed in the north-eastern subpolar North Atlantic. Here, we present a diatom-based sea surface temperature reconstruction from the Iceland Basin, south of Iceland; the reconstruction shows the warmest temperatures of the record at 6.1–4 ka BP, cooler temperatures at 4-2 ka BP and warmer temperatures thereafter. Inter-record comparisons indicate that the cold period at c. 4-2 ka BP may have resulted from a strengthened East Greenland Current and/or melting of the Greenland ice sheet, in response to a negative North Atlantic Oscillation. The findings highlight that atmospheric circulation changes are likely to cause pronounced variations in the latitudinal exchange of heat, which may have consequences for deep-water formation and global ocean circulation. Highlights: Sea surface temperature in the Iceland Basin shows millennial variability. Colder temperatures between 4000 and 2000 years ago. Record comparison shows cold interval to the west of the subpolar North Atlantic. Coincides with negative North Atlantic Oscillation suggesting atmospheric forcing. Stronger East Greenland Current or Greenland melting possible causes.